Utilization of open educational resources (OERs) among college students affiliated to Alagappa university in India - Nagaiah, M.; Thanuskodi, S. (Linguistics and Culture Review, 2021)
The world is now paralyzed by covid-19 (2021). UNESCO estimates that there are more than 1.5 billion students in 165 countries and that 87% of the world's students are at risk of contracting the covid-19 pandemics. Open education resources help students continue to study in such situations. This article provides information on what are open education resources, how to use open education resources, and what to do for research. Furthermore, this research report is about how Alagappa University students use open education resources and how it benefits them. What are the barriers they face to obtain OER information? This study aims to provide students with a brief overview of awareness and use of open education resources. A sample of the respondents was prepared from Alagappa University students. Questionnaires were made by Google Forms. A total of 245 Google Forms were sent to students via WhatsApp and Gmail, and 121 students responded. Frequency of use of OER: 72 students use OER daily, 18 students use it twice a week, 27 students use it weekly and 4 students use it monthly.